DESAIN MEDIA PROMOSI DAN KOMUNIKASI VISUAL PADA YAYASAN SMK ISLAM BAIDHAUL AHKAM KOTA TANGERANG - Andriyanto Andriyanto; Dianarti Muhyani (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2019)
Through media images, colors, and information texts become more clear and interesting. Especially in the field of publications, multimedia has become one of the supporting media in the delivery of effective, and more interesting information in its presentation. From time to time, people's needs for creative, efficient and effective designs are increasing. The development of the world of education is increasingly rapid, leading to the increasing number of facilities and advantages that must be promoted to compete with other schools, especially at the Baidhaul Ahkam Islamic Vocational School foundation. Current problems in the Baidhaul Ahkam Islamic Vocational School, in its promotional strategy, still use less informative designs for new prospective students, making them less interested in seeing Baidhaul Ahkam Islamic Vocational Schools. The research method used is observation, interview and literature study. Through a more attractive and up-to-date design design, it is expected that new students can find out updated information and are interested in attending Baidhaul Ahkam Islamic Vocational School and becoming more widely known to the wider audience.